(untitled) - Escoe, A. Keith (Amsterdam, 2006)
A comprehensive volume on piping and pipelines, never before published in the process industries in this format.
Keywords: Piping,Pipelines,Đường ống; Maintenance and repair,Maintenance and repair,Bảo trì và sửa chữa